High-field magnetization and magnetoresistance of the honeycomb Kondo lattice alloys Ce(Pt1-xPdx)6Al3. Issue 1 (1st March 2022) - Oishi, R.; Miyake, A.; Tokunaga, M.; Shimura, Y.; Umeo, K.; Onimaru, T.; Takabatake, T.
Abstract: CePt6 Al3 is a rare example of the Ce-based honeycomb lattice compound. Substitution of the isovalent Pt for Pd transforms the ground state from a paramagnetic heavy-fermion state to an antiferromagnetic (AFM) ordered state. To gain insight into the role of magnetic frustration in the honeycomb Kondo lattice, we have measured the magnetization M(B) and electrical resistivity ρ ( B ) of Ce(Pt1- x Pd x )6 Al3 ( x ≤ 0.3) in pulsed magnetic fields up to 60 T. For the single crystal with x = 0, M ( B ) for B along the easy c axis exhibits a metamagnetic increase and ρ ( B || c ) bends at Bm = 28 T. Taking the temperature at a shoulder in the magnetic susceptibility χ ( ल ) for B ‖ c as T χ m = 17 K, the ratio μ B B m / K B T >χ m is estimated to be 1.1. This value agrees with those reported for Ce-based paramagnetic heavy-fermion compounds with similar magnitudes of B m . With increasing x from 0 to 0.3 in polycrystalline samples, the magnitude of M ( B = 60 T) at 1.4 K increases from 0.75 to 2.0 μ β /Ce, indicating the recovery of localized 4 f moments by the Pd substitution for Pt. Using the data of M ( B ) and ρ ( B ) for x = 0.1, 0.2, 0.3, we constructed B-T phase diagrams, which show a trend from a small moment AFM ordered state for x = 0.1 to a large moment AFM ordered state for x = 0.3.